2009
DOI: 10.1128/iai.00652-09
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Potentials of an Intrinsically Unstructured Fragment Derived from the Blood Stage-Associated Plasmodium falciparum Protein PFF0165c

Abstract: We have identified new malaria vaccine candidates through the combination of bioinformatics prediction of stable protein domains in the Plasmodium falciparum genome, chemical synthesis of polypeptides, in vitro biological functional assays, and association of an antigen-specific antibody response with protection against clinical malaria.Within the predicted open reading frame of P. falciparum hypothetical protein PFF0165c, several segments with low hydrophobic amino acid content, which are likely to be intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…1A; see Table S1 in the supplemental material) were used to isolate human monoclonal and polyclonal antibodies. In addition, monoclonal antibodies were isolated on peptide 27, an alpha-helical coiled-coil from the vaccine candidate PFF0165c (34,39,61). Screening for monoclonal antibodies was performed by ELISA using 12-day supernatants of CD22…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A; see Table S1 in the supplemental material) were used to isolate human monoclonal and polyclonal antibodies. In addition, monoclonal antibodies were isolated on peptide 27, an alpha-helical coiled-coil from the vaccine candidate PFF0165c (34,39,61). Screening for monoclonal antibodies was performed by ELISA using 12-day supernatants of CD22…”
Section: Resultsmentioning
confidence: 99%
“…These were compared for wild-type (WT) and Fc domain mutant monoclonal antibodies to both MSP2 and an alpha-helical coiled-coil (peptide 27) from the gene PFF0165c. Peptide 27 has recently been identified to be a novel, highly conserved, P. falciparum vaccine candidate (34,39,61). Contrary to prediction, a remarkably high level of heterologous function by allele-specific MSP2 human antibodies was observed.…”
mentioning
confidence: 88%
“…This could possibly result in the generation of conformational B-cell epitopes, but our results suggest that this is not a frequent occurrence, and in contrast to the dominance of conformational B-cell epitopes in globular proteins, linear epitopes predominate in MSP2 and presumably other intrinsically unstructured proteins. This is of particular relevance to malaria vaccine development, given the abundance of unstructured proteins in Plasmodium proteomes (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…This approach was adopted rather than taking a genome-wide approach, which predominantly includes intracellular proteins, because the role of intracellular proteins as targets of protective or functionally active Abs is unclear. Although it was demonstrated that immune responses against intracellular proteins can induce inhibition of in vitro parasite growth by ADCI mechanisms (66,67), we sought to focus on Ags that are likely to be direct targets of Abs to intact merozoites. Genome-wide approaches using high-throughput protein expression are also valuable and have identified Ags that may be important immune targets or biomarkers of immunity (15).…”
Section: Discussionmentioning
confidence: 99%